Pelatihan Manajemen Usaha dan Pemasaran Digital untuk Penguatan Kapasitas Organisasi BUMDes dalam Pengembangan Ekonomi Lokal di Desa Serang, Kecamatan Cikarang Selatan - Auliani Khoirunnisa (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Community service activities to enhance the organizational capacity of Village-Owned Enterprises (BUMDes) in supporting local economic development through business management and digital marketing training in Serang Village, Cikarang Selatan Subdistrict. The method used was a participatory approach with a descriptive qualitative approach, aimed at encouraging active involvement of BUMDes managers and village communities in every stage of the activity. Data collection techniques included field observations, in-depth interviews, and documentation, with a focus on changes in BUMDes organizational capacity before and after the intervention. The results showed that BUMDes faced structural, technical, and institutional weaknesses, such as an unsystematic organizational structure, weak leadership, lack of business plans, and low adoption of digital technology. After the training, there was a significant improvement in organizational structure, strategic planning, financial accountability, and the use of digital platforms for marketing. The activity also succeeded in fostering a more participatory and innovative organizational culture and expanding strategic partnership networks. This transformation had a direct impact on improving the economic performance of BUMDes and community participation, making BUMDes a facilitator of inclusive local economic collaboration. These findings indicate that an integrated training approach is an effective strategic model for strengthening village economic institutions sustainably.